Animal Models of Stroke - Hoyte, L; Buchan, A (Elsevier, 2010)
Stroke is the third leading cause of death and a major cause of disability in western nations. Stroke animal models are used to approximate the human condition and to give insight into the development of pathology and possible treatment pathways. The vast majority of stroke modeling is performed in rodents, and less frequently in higher order mammals such as dogs, cats, and nonhuman primates. © 2009 Elsevier Ltd All rights reserved.